Exogenous L-Arginine Enhances Pathogenicity of Alternaria alternata on Kiwifruit by Regulating Metabolisms of Nitric Oxide, Polyamines, Reactive Oxygen Species (ROS), and Cell Wall Modification - Di Wang; Lingkui Meng; Haijue Zhang; Rong Liu; Yuhan Zhu; Xinyu Tan; Yan Wu; Qingchao Gao; Xueyan Ren; Qingjun Kong (Journal of Fungi)
Black spot, one of the major diseases of kiwifruit, is caused by Alternaria alternata. A comprehensive investigation into its pathogenicity mechanism is imperative in order to propose a targeted and effective control strategy. The effect of L-arginine on the pathogenicity of A. alternata and the underlying mechanisms were investigated. The results showed that treatment with 5 mM L−1 of L-arginine promoted spore germination and increased the colony diameter and lesion diameter of A. alternata in vivo and in vitro, which were 23.1% and 9.3% higher than that of the control, respectively. Exogenous L-arginine treatment also induced endogenous L-arginine and nitric oxide (NO) accumulation by activating nitric oxide synthase (NOS), arginine decarboxylase (ADC) and ornithine decarboxylase (ODC). In addition, exogenous L-arginine triggered an increase in reactive oxygen species (ROS) levels by activating the activity and inducing gene expression upregulation of NADPH oxidase. The hydrogen peroxide (H2O2) and superoxide anion (O2.−) levels were 15.9% and 2.2 times higher, respectively, than in the control group on the second day of L-arginine treatment. Meanwhile, antioxidant enzyme activities and gene expression levels were enhanced, including superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), glutathione peroxidase (GPX), and glutathione reductase (GR). In addition, exogenous L-arginine stimulated cell wall-degrading enzymes in vivo and in vitro by activating gene expression. These results suggested that exogenous L-arginine promoted the pathogenicity of A. alternata by inducing the accumulation of polyamines, NO, and ROS, and by activating systems of antioxidants and cell wall-degrading enzymes. The present study not only revealed the mechanism by which low concentrations of L-arginine increase the pathogenicity of A. alternata, but also provided a theoretical basis for the exclusive and precise targeting of A. alternata in kiwifruit.